k+n=x

Simple and best practice solution for k+n=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for k+n=x equation:


Simplifying
k + n = x

Solving
k + n = x

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-1n' to each side of the equation.
k + n + -1n = -1n + x

Combine like terms: n + -1n = 0
k + 0 = -1n + x
k = -1n + x

Simplifying
k = -1n + x

See similar equations:

| (z-5)(z+4)=36 | | 2x+7y=-19 | | ln(x)=.33 | | (X+3)/(4x-5) | | 7/5/8 | | 15z^2-53z=28 | | m-33=-18 | | 3(3x-9)/2=5(9x/3)/4 | | 6/11x=128 | | h(t)=20-16tsquared+32t | | 2(4x+5)=35 | | 6x+6=4-bracket(5x-4) | | B^2+6n+8=0 | | 5(x+4)+2=47 | | 210+344= | | 4(x+1)-2x=-4 | | 51=9-7x | | 4c-6=6c+14 | | -5x-6=-46 | | 98.31/49.1/4 | | y=-1(0)+8 | | 3(0)-9y=9 | | 32x-(3x^2)=-35 | | 9x+24=-7x-8 | | -3(0)+4y=-12 | | -3x+4(0)=-12 | | -11x+129=-x-3+2x | | 2(-7)+5(3)=1 | | .5x+3=-10 | | -7x+9=2x | | 2(-4)+5(1)=1 | | y^2+20y-100=0 |

Equations solver categories